Vermicast of Earthworm as Ecosystem Engineers within Different Vermireactor Shape - Kilowasid, Laode Muhammad Harjoni; Sanjaya, Muhammad Fahyu; Rakian, Tresjia Corina; Alam, Syamsu; Djafar, Muhammad Kabil; Muliddin, Muliddin (JOURNAL OF TROPICAL SOILS, 2020)
Earthworms as ecosystem engineers can modify the quality of vermibed assembled from mixed soil with organic material in a vermireactor. Various in shapes of the vermireactor are used to produce a vermicast for biofertilizer in agriculture. The objective of this research was to study the vermicast production and its quality produced from a variety of vermireactor shapes. Earthworm (Pheretima sp.) which was applied to the vermireactor consists of: with- and without of earthworms. Three shapes of the vermireactor, namely cylinder, square, and rectangular has been tested. Compost of Chromolaena odorata pruning mixed with soil was used as vermibed. The vermicast process ran until 28 days. The results showed that vermireactor with earthworms which were successfully converted to vermicast was about 49.24% from the vermibed volume, however, no vermicast formed was found from vermireactor without earthworms. The difference in vermicast produced from different vermireactor shapes was not significant. The value of pH, total-N, and C/N ratio among the vermicast was different. The number of the morphological character of bacteria colonies in the vermicast produced from the square vermireactor was the highest, while from cylinder vermireactor was the lowest. We concluded that the quality of vermicast from earthworm (Pheretima sp.) activity was determined by the shape of the vermireactor.